2018
DOI: 10.21037/gs.2017.11.08
|View full text |Cite
|
Sign up to set email alerts
|

The prostate cancer focal therapy

Abstract: Despite prostate cancer (PCa) is the leading form of non-cutaneous cancer in men, most patients with PCa die with disease rather than of the disease. Therefore, the risk of overtreatment should be considered by clinicians who have to distinguish between patients with high risk PCa (who would benefit from radical treatment) and patients who may be managed more conservatively, such as through active surveillance or emerging focal therapy (FT). The aim of FT is to eradicate clinically significant disease while pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 146 publications
(235 reference statements)
0
11
0
Order By: Relevance
“…During the ablation process, adjacent organs and structures, including the urethra, bladder and rectum, could be affected and injured. Urinary retention, urinary incontinence, recto-urethral fistula, urethral strictures and erectile dysfunction may occur after ablation in short or long period [25,26]. According to the focal LA of prostate cancer in phase I and II trials, the most common complications include haematuria, perineal ecchymosis or abrasion, glans paraesthesia, acute urinary incontinence and sexual dysfunction [27,28].…”
Section: Plos Onementioning
confidence: 99%
“…During the ablation process, adjacent organs and structures, including the urethra, bladder and rectum, could be affected and injured. Urinary retention, urinary incontinence, recto-urethral fistula, urethral strictures and erectile dysfunction may occur after ablation in short or long period [25,26]. According to the focal LA of prostate cancer in phase I and II trials, the most common complications include haematuria, perineal ecchymosis or abrasion, glans paraesthesia, acute urinary incontinence and sexual dysfunction [27,28].…”
Section: Plos Onementioning
confidence: 99%
“…The TFC core concept of active intra-procedural fusion image correction may potentially be applied to other procedures, settings, or organs with additional hardware components and software [18]. The TFC ability to maintain accurate image alignment after motion could not only benefit existing procedures using fusion imaging (FBx, trans-perineal FBx, focal PCa ablations), but also potentially enable fusion guidance within robotic platforms [8,12,15,16,[19][20][21][22][23][24][29][30][31]. In addition to aid in alignment after simulated prostate motion, this study also indicated that the TFC may aid in more accurate image alignment while the patient remains static.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, computer-assisted biopsy systems may facilitate more widespread and standardised use of FBx, even by novice operators who may be uncomfortable manipulating dedicated navigation software [25,32]. On the other hand, some intrinsic limitations are still present such as the general contraindications for MRI (e.g., the claustrophobia and the presence of a magnetic field or of the pacemakers) and the current failure rate of TRUS-guided biopsy [12,[33][34][35][36]. Additional research may explore the extent to which the TFC aids in fusion image alignment when the prostate is static, specifically among novice FBx users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a lot of new IR procedures are being applied to prostate gland from invasive diagnosis to treatment of benign and malign diseases (6)(7)(8).…”
mentioning
confidence: 99%